Comparing high‐resolution microscopy techniques for potential intraoperative use in guiding low‐grade glioma resections. Issue 4 (14th April 2015) - Meza, Daphne; Wang, Danni; Wang, Yu; Borwege, Sabine; Sanai, Nader; Liu, Jonathan T. C.
Abstract : Background and Objectives: Fluorescence image‐guided surgery (FIGS), with contrast provided by 5‐ALA‐induced PpIX, has been shown to enable a higher extent of resection of high‐grade gliomas. However, conventional FIGS with low‐power microscopy lacks the sensitivity to aid in low‐grade glioma (LGG) resection because PpIX signal is weak and sparse in such tissues. Intraoperative high‐resolution microscopy of PpIX fluorescence has been proposed as a method to guide LGG resection, where sub‐cellular resolution allows for the visualization of sparse and punctate mitochondrial PpIX production in tumor cells. Here, we assess the performance of three potentially portable high‐resolution microscopy techniques that may be used for the intraoperative imaging of human LGG tissue samples with PpIX contrast: high‐resolution fiber‐optic microscopy (HRFM), high‐resolution wide‐field microscopy (WFM), and dual‐axis confocal (DAC) microscopy. Materials and Methods: Thick unsectioned human LGG tissue samples (n = 7) with 5‐ALA‐induced PpIX contrast were imaged using three imaging techniques (HRFM, WFM, DAC). The average signal‐to‐background ratio (SBR) was then calculated for each imaging modality (5 images per tissue, per modality). Results: HRFM provides the ease of use and portability of a flexible fiber bundle, and is simple and inexpensive to build. However, in most cases (6/7), HRFM is not capable of detecting PpIX signal from LGGs due to high autofluorescence, generated by the fiber bundle under laser illumination at 405 nm, which overwhelms the PpIX signal and impedes its visualization. WFM is a camera‐based method possessing high lateral resolution but poor axial resolution, resulting in sub‐optimal image contrast. Conclusions: Consistent successful detection of PpIX signal throughout our human LGG tissue samples (n = 7), with an acceptable image contrast (SBR >2), was only achieved using DAC microscopy, which offers superior image resolution and contrast that is comparable to histology, but requires a laser‐scanning mechanism to achieve optical sectioning. Lasers Surg. Med. 47:289–295, 2015. © 2015 Wiley Periodicals, Inc.